PERAN KEPALA SEKOLAH DALAM MENERAPKAN MANAJEMEN MUTU TERPADU (TQM) PADA LEMBAGA PENDIDIKAN ISLAM - Ula, Wardah Febrianas; Khusnia, Rismatul; Qommaruddin, Muhammad; Yuana, Orchida Aprila (STKIP Pesisir Selatan, 2025)
This study aims to analyze the role of school principals in implementing Total Quality Management (TQM) in Islamic educational institutions. The implementation of TQM is essential as Islamic schools are required to continuously improve the quality of educational services in order to meet stakeholders’ expectations and remain competitive. This research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, observations, and document analysis, involving the school principal as the key informant, supported by teachers and educational staff. The data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings reveal that the school principal plays a strategic role in the implementation of TQM through the formulation of quality-oriented vision and policies, the development of a quality culture, the empowerment of human resources, and the execution of continuous evaluation and improvement. Effective leadership in TQM implementation has a positive impact on the quality of learning processes, teachers’ performance, and public trust in Islamic educational institutions. The novelty of this study lies in revealing a contextual model of TQM implementation that is integrated with Islamic values, contributing to the development of quality-based leadership in Islamic education.